Intracerebral Hemorrhage after Intravenous Thrombolysis in Patients with Cerebral Microbleeds and Cardiac Myxoma - Chutinet, Aurauma; Roongpiboonsopit, Duangnapa; Suwanwela, Nijasri C. (Frontiers in Neurology, 2014)
ABSTRACT Background and Purpose: Cardiac myxoma is a rare etiology of stroke. Both cerebral microbleeds and cardiac myxoma may increase the risk of intracerebral hemorrhage after intravenous thrombolysis. However, data is still limited. We report a case of multiple cerebral microbleeds treated with intravenous thrombolysis with later findings of cardiac myxoma. Summary of case: A 58-year-old-man presented with right-sided hemiplegia and global aphasia. The presumptive diagnosis of acute left middle cerebral artery infarction was made. Previous MRI showed multiple cerebral microbleeds. The patient received intravenous thrombolysis. Intracranial hemorrhage occurred in bilateral cerebellums after thrombolysis and a median suboccipital craniectomy and hematoma removal was performed. Transthoracic echocardiogram found a left atrial myxoma. The tumor was then surgically removed. The neurological deficits improved 6 months later. Conclusion: Cerebral microbleeds may be associated with atrial myxoma. Intravenous thrombolysis could benefit acute ischemic stroke patients with both baseline cerebral microbleeds and atrial myxoma.